Critical conditions leading to puffing and micro-explosion of composite liquid droplets; International Communications in Heat and Mass Transfer; Vol. 156 - Antonov D. V. Dmitry Vladimirovich; Vysokomornaya O. V. Olga Valeryevna; Yanovsky (Yanovskiy) Leonid Samoylovich L. S.; Strizhak P. A. Pavel Alexandrovich (2024, 2024)
Title screen